The calculation of a living wage: the UK's experience. (August 2019) - D'Arcy, Conor; Finch, David
Translating the concept of a living wage into a cash figure presents a number of challenges. A recent review of the approaches used in the UK explored these, with the aim of creating a unified and improved calculation. Designing a living wage relies on some technical decisions, such as which data sources are most appropriate. But many of the building blocks underlying a living wage require judgements on societal values, expectations and norms. The living wage rates in the UK are voluntary and promoted by campaign groups; this means any methodology needs to be empirically sound but also recognise the realities facing employers. No perfect approach can exist. But through analysis, consultation with stakeholders and a clear governance structure, the method used in London and the rest of the UK offers a robust, respected and up-to-date way to calculate the income needed to meet a decent standard of living.